(untitled) (AYUSHDHARA, 2019)
The disease Urdhvagha Amlapitta is a common functional disease of Annavaha srotas due to irregular, improper food habits and busy stressful lifestyle. This disease is a constant challenge to treat because of its recurrence nature due to faulty dietary habits. The management of this disease is somewhat difficult and patients are looking with a hope towards Ayurveda to overcome this challenge. So, this study was designed as a placebo controlled double blind trial to evaluate the efficacy of Katuki and Sita Churna capsules in Urdhvagha Amlapitta. 30 patients of Urdhvaga Amalpitta were selected and randomly allocated in two groups. Group A received Katuki and Sita capsules and group B received placebo capsules, both in the dose of two capsules twice daily before food for 30 days. It is observed that Urdhvagha Amlapitta is seen in middle age and most common in females. It is usually seen in those whose lifestyle is not fixed and having irregular food habits. All 30 patients had completed the treatment and no adverse effects were reported during the treatment. After statistical analysis the inter group difference were insignificant in all parameters after the end of treatment period except Hrit/Kanta daha where in difference was slightly significant with more improvement in group A than the group B. By the overall result we can conclude that Katuki and Sita capsules are having significant effect in the Urdhvaga Amlapitta.